Promoting anaerobic biogasification of corn stover through biological pretreatment by liquid fraction of digestate (LFD). (January 2015) - Hu, Yun; Pang, Yunzhi; Yuan, Hairong; Zou, Dexun; Liu, Yanping; Zhu, Baoning; Chufo, Wachemo Akiber; Jaffar, Muhammad; Li, Xiujin
Highlights: Biogasification of liquid fraction of digestate pretreated corn stover was studied. 17.6% TS content and ambient temperature was appropriate for pretreatment. 3-days was considered to be optimal for pretreatment. Considerable LCH contents reductions were observed during pretreatment. CH4 production yields and rates significantly increased after pretreatment. Abstract: A new biological pretreatment method by using liquid fraction of digestate (LFD) was advanced for promoting anaerobic biogasification efficiency of corn stover. 17.6% TS content and ambient temperature was appropriate for pretreatment. The results showed that C/N ratio decreased to about 30, while total lignin, cellulose, and hemicellulose (LCH) contents were reduced by 8.1–19.4% after pretreatment. 3-days pretreatment was considered to be optimal, resulting in 70.4% more biogas production, 66.3% more biomethane yield and 41.7% shorter technical digestion time compared with the untreated stover. The reductions on VS, cellulose, and hemicellulose were increased by 22.1–35.9%, 22.3–35.4%, and 19.8–27.2% for LFD-treated stovers. The promoted anaerobic biogasification efficiency was mainly attributed to the improved biodegradability due to the pre-decomposition role of the bacteria in LFD. The method proved to be an efficient and low cost approach for producing bioenergy from corn stover, meanwhile, reducing LFD discharge and minimizing its potential pollution.